Decreased Vancomycin MICs among Methicillin-Resistant Staphylococcus aureus Clinical Isolates at a Chinese Tertiary Hospital over a 12-year Period - Lu, Chaohui; Guo, Yinjuan; Wang, Shanshan; Wang, Zhengzheng; Chen, Lan; Lv, Jinnan; Qi, Xiuqin; Chen, Zengqiang; Han, Lizhong; Zhang, Xueqing; Wang, Liangxing; Yu, Fangyou (Frontiers in Microbiology, 2016)
The increased vancomycin minimum inhibitory concentration values (MICs) for methicillin-resistant Staphylococcus aureus (MRSA) isolates are associated with treatment failure and mortality of MRSA infections. In the present study, 553 non-duplicate MRSA isolates from various specimens of patients with infections at a Chinese tertiary hospital from January 2003 to December 2014, were selected randomly for investigating the shift of vancomycin MICs determined by E-test method. The percentages of the MRSA isolates with vancomycin MICs of ≥ 2.0 mg/L, 1.5 mg/L, 1.0 mg/L and ≤0.75 mg/L were 16.3% (90/553), 38.5% (213/553), 35.6% (197/553) and 9.9% (55/553), respectively. The highest geometric mean MIC (GM MIC) value (1.648 mg/L) and the lowest GM MIC (0.960 mg/L) were found in the first year (2003) and the last year (2014) over the study period, with significant difference (p<0.05). The GM MICs over the study period fluctuated by year, with the elevated values in 2005, 2011 and 2013 and the decreased values in other years relative to the respective former year. The vancomycin GM MIC (1.307 mg/L) for MRSA isolates from sputum was the highest relative to that for the MRSA isolates from other specimens. By contrast, the vancomycin GM MIC value (1.156 mg/L) for MRSA isolates from pus was the lowest, with similar value to that for the isolates from blood. The vancomycin GM MICs in period Ⅰ(2003-2005), period Ⅱ(2006-2008), period Ⅲ (2009-2011) and period Ⅳ (2012-2014) were 1.501 mg/L, 1.345 mg/L, 1.177 mg/L and 1.139 mg/L, respectively, with the continuous decreased trend. Compared with period Ⅰ, the vancomycin GM MIC for MRSA isolates in period Ⅳ was significantly lower (p<0.01), with a 1.318- fold decrease. The percentages of the isolates with vancomycin MIC ≥ 2 mg/L in 4 periods were 25%, 15.6%, 15.2%, and 12%, respectively, with a continuous decrease. While the percentages of the isolates with vancomycin MIC ≤0.75 mg/L in 4 periods increased from 1.7% in period Ⅰ to 19.3% in period Ⅳ. Taken together, a decreased trend in vancomycin MICs for MRSA isolates from a Chinese tertiary teaching hospital has been found. This pnenomenon was mainly associated with a decrease in the